SURVIVAL STUDY ON TRAFFIC AWARE RESOURCE OPTIMIZED ROUTING IN WIRELESS SENSOR NETWORK. - BALASUBRAMANI, S.; REKHA, C. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Wireless sensor network includes the small low-cost sensor nodes with restricted broadcast range and their processing, storage competences. The network collects information from the nodes and sends data to base station for processing. Wireless message is one of the major power overwhelming events on sensor nodes and its usage is measured by direction-finding protocol. Direction-finding protocol is used to transmit the data from basis node to destination node. During the data transmission, traffic remained unaddressed and energy consumption was not reduced. In order to address these problems, traffic aware resource optimized routing is carried out using machine learning techniques with minimum energy consumption and delay.